Robert College of Constantinople: crossroads of faiths, cultures, and empires, 1863-1913 - Petrov, Nick (Lexington Books, 2023)
"Robert College of Constantinople is the oldest American school still in existence in its original location outside the borders of the United States. The history of the College includes 160 years of originality, innovations, and astonishing development that impacted the history of Armenia, Bulgaria, Greece, the Ottoman Empire, and the United States of America"--